THE USE OF YELLOW KEPOK BANANA PEEL EXTRACT (MUSA PARADISIACA L. VAR BLUGGOE) AS AN ANTIBACTERIAL FOR CHRONIC PERIODONTITIS CAUSED BY PORPHYROMONAS GINGIVALIS - Sutanti, Viranda; Destyawati, Arum Anugrah (JSMARTech, 2019)
Chronic periodontitis is the most common periodontal disease, and Porphyromonas gingivalis is its dominant causative microorganism. Yellow kepok banana peel (Musa Paradisiaca L. Var. Bluggoe) contains flavonoids, alkaloids, tannins, saponins and triterpenoids that can inhibit and kill Porphyromonas gingivalis. Purpose: To reveal the antibacterial effectiveness of yellow kepok banana peel extract against Porphyromonas gingivalis. Method: This is true experimental research employing the post-test only control group approach. Preliminary research was conducted to determine the concentration of the sample group, 6 treatment groups (5%, 7.5%, 10%, 12.5%, 15%, 17.5%), and 2 control groups were involved. Yellow kepok banana peel extract was obtained through the maceration method using methanol as a solvent. The antibacterial activity was identified using the tube dilution method. Data analysis was conducted through the Kruskal Wallis test, the Mann Whitney test, and the Spearman correlation test. Result: Minimum Inhibitory Concentration (MIC) is obtained at a concentration of 10%, while the Minimum Bactericidal Concentration (MBC) is obtained at a concentration of 17.5%. The test results of tube turbidity statistics indicated that there were significant differences in each extract concentration and there was a relationship between the concentration variables and the turbidity of the tubes. The statistical test results of the colony growth revealed that there were significant differences in each extract concentration and there was a relationship between the concentration variables and the growth of bacterial colonies. Conclusion: Yellow kepok banana peel extract (Musa paradisiaca L. var. Bluggoe) is effective to use as antibacterial for chronic periodontitis caused by Porphyromonas gingivalis.